Sr[Mg3SiN4]Eu2+ phosphor: solution for enhancing the optical properties of the 5600K remote-packaging WLEDs - Phu Tran Tin; Duy Hung Ha; Minh Tran (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
In the last decade, light-emitting diodes (LEDs), which based on spontaneous light emission in semiconductors can be considered as the main light sources for civil and industrial purposes. In this paper, we presented and investigated the effect of the Sr[Mg3SiN4]Eu2+ concentration on the optical properties of the 5600K remote-packaging WLEDs (RP-WLEDs). We use the Mat Lab and the LightTool software to investigate the effect of the Sr[Mg3SiN4]Eu2+ concentration on the CRI, CQS, D-CCT and LO of the 5600K RP-WLEDs. From the result, we can state that the concentration of the Sr[Mg3SiN4]Eu2+ influenced on the CRI, CQS, D-CCT and LO of the RP-WLEDs. The red Sr[Mg3SiN4]Eu2+ phosphor can be considered as the novel recommendation for LEDs industry.